Potensi Daun Trembilungan (Begonia hirtella Link) sebagai Antibakteri dan Antifungi - Febri Nur Ngazizah; Nuraeni Ekowati; Aisyah Tri Septiana (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Begonia hirtella leaf are commonly used by people in mountainous areas to treat itchy due to insect bites and skin infection. This study aims to (1) determine proper solvent extract of B. hirtella leaf on antibacterial activity of S. aureus and E. coli and on antifungal activity of C. albicans (2) determine the lowest concentration of leaf extract of B. hirtella that indicate the formation of inhibition zone (3) know the content of bioactive compounds contained in each leaf extract of B. hirtella. The method used in this study is experimental with completely randomized design (CRD). The treatments were type of solvents (n-hexane, ethyl acetate, ethanol and water) and a serie of the ethyl acetate extract concentration of 500 ppm, 450 ppm, 400 ppm, 350 ppm, 300 ppm and 250 ppm against S. aureus, E. coli and C. albicans. Data were analyzed using analysis of variance (Anova) and the significant differences between the treatments were analyzed by Duncan test at 95% confidence level. The result showed that each solvent extracts affect microbes growth with a highly significant difference p <0.05. Solvent extracts that have the best inhibitory zone is ethyl acetate against S. aureus with an average diameter of inhibitory zone 13.75 ± 1.26 mm. Increasing concentrations of ethyl acetate extract of 250 ppm to 500 ppm increase inhibition zone against microbes. The lowest concentration that show inhibition zone was 300 ppm. The formation inhibition of zone on microbes growth happened due to their compounds in the extract. Extract of n-hexane contains stigmasterol, ethyl acetate contains neophytadiene, while the ethanol extract contains ethyl palmitate